2022
DOI: 10.1136/rmdopen-2022-002479
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and cellular SARS-CoV-2 vaccine responses in patients with giant cell arteritis and polymyalgia rheumatica

Abstract: ObjectivesGiant cell arteritis (GCA) and polymyalgia rheumatica (PMR) are overlapping autoinflammatory diseases affecting people over 50 years. The diseases are treated with immunosuppressive drugs such as prednisolone, methotrexate, leflunomide and tocilizumab. In this study, we assessed the immunogenicity and safety of SARS-CoV-2 vaccinations in these diseases (based on humoral and cellular immunity).MethodsPatients (n=45 GCA, n=33 PMR) visited the outpatient clinic twice: pre-vaccination and 4 weeks after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…A possible explanation for the accelerated waning may be that prednisolone impairs the antigen presentation and germinal center reactions that are required for long-lasting immune responses, whereas methotrexate has more effect on B cells only. This is supported by the findings in our primary study, which showed impaired cellular immunity in GCA/PMR patients taking ≥10 mg/day of prednisolone, but not in those taking methotrexate (6).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…A possible explanation for the accelerated waning may be that prednisolone impairs the antigen presentation and germinal center reactions that are required for long-lasting immune responses, whereas methotrexate has more effect on B cells only. This is supported by the findings in our primary study, which showed impaired cellular immunity in GCA/PMR patients taking ≥10 mg/day of prednisolone, but not in those taking methotrexate (6).…”
Section: Discussionsupporting
confidence: 84%
“…EULAR guidelines have named prednisolone and methotrexate among the few immunosuppressive drugs that likely impact vaccine immunogenicity. Our previous study in GCA and PMR patients, in congruence with further studies in these patients, highlighted that methotrexate and higher dosages of prednisolone associated with hampered humoral vaccine responses (4)(5)(6), and in patients using >10 mg/day prednisolone, also cellular immunity was impaired.…”
Section: Introductionsupporting
confidence: 61%
See 3 more Smart Citations